2011
DOI: 10.1108/15982681111140598
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and ranking critical success factors for implementation of total quality management in the Indian manufacturing industry using TOPSIS

Abstract: PurposeThe purpose of this paper is to review critical success factors (CSFs) of total quality management (TQM), and to rank these in the Indian manufacturing industry.Design/methodology/approachTo rank the CSFs, Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was used. The data were collected using questionnaires as the research instrument.FindingsProcess management, top management leadership and customer focus are the top three factors for implementation of TQM in the manufacturing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 63 publications
2
28
0
1
Order By: Relevance
“…The management must be aware of their workforce and also give motivation to them to improve their performance. As stated in the findings in the previous study, TQM is a managerial approach and without the support from the organizational leaders, the implementation of TQM would not succeed [33] The finding is in line with other studies such as [34] and [35].…”
Section: J Management Supportsupporting
confidence: 86%
“…The management must be aware of their workforce and also give motivation to them to improve their performance. As stated in the findings in the previous study, TQM is a managerial approach and without the support from the organizational leaders, the implementation of TQM would not succeed [33] The finding is in line with other studies such as [34] and [35].…”
Section: J Management Supportsupporting
confidence: 86%
“…An eminent subset of soft factors which primarily deals with behavioural and humanitarian aspects of management is CSFs (Saljoughian et al, 2014). Rahman and Tannock (2005) as well as Lewis et al (2006) Khanna et al (2011) introduced top management leadership, supplier's quality management, human resources management, process management, customers focus, role of quality department, product design, quality information system and use of IT, training and quality citizenship as CSFs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Akgun et al [30], based on a sample of 193 firms in Turkey, demonstrated that there is an interconnected relationship among TQM, organizational learning capability (OLC), business innovativeness, and a firm's financial performance and proposed that OLC and business innovativeness mediate the relationship between TQM and a firm's financial performance. Other authors [31] reviewed the critical success factors of TQM, and ranked these in the Indian manufacturing industry using a technique for order preference by similarity to an ideal solution. Using a sample of TQM companies operating in mainland China, Hong Kong, and Taiwan, Noronha [32] found that adaptiveness, harmony with people, harmony with the universe, interdependence, and respect for authority have important influences on four quality dimensions, namely climate, processes, methods, and results.…”
Section: Introductionmentioning
confidence: 99%